2007
DOI: 10.1007/s10750-007-9240-9
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton seasonal variation in a shallow stratified eutrophic reservoir (Garças Pond, Brazil)

Abstract: This study aimed at describing the phytoplankton dynamics and structure in a shallow eutrophic reservoir, the Garças Pond, located in the Parque Estadual das Fontes do Ipiranga (23°38 0 40.6 00 S, 46°37 0 28.0 00 W), in the Municipality of São Paulo, southeast Brazil. Samples were collected monthly from January to December 1997 in five depths (subsurface, 1 m, 2 m, 3 m, and 20 cm above the bottom) in the pelagic zone (Z max = 4.7 m). Abiotic variables studied were: water temperature, turbidity, transparency, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
39
0
12

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 67 publications
7
39
0
12
Order By: Relevance
“…In this study, M. aeruginosa dominated when the temperature varied between 25.21 and 27.41°C. It was positively correlated with pH, in accordance with the literature (Fonseca and Bicudo 2008). The M group adapts to high light availability expressed as high values of Zeu/ Zmix when M group dominated, and there are other studies suggesting that the species in M groups such as M. aeruginosa occur in enriched lakes and are tolerant to low light availability BovoScomparin and Train 2008).…”
Section: Discussionsupporting
confidence: 88%
“…In this study, M. aeruginosa dominated when the temperature varied between 25.21 and 27.41°C. It was positively correlated with pH, in accordance with the literature (Fonseca and Bicudo 2008). The M group adapts to high light availability expressed as high values of Zeu/ Zmix when M group dominated, and there are other studies suggesting that the species in M groups such as M. aeruginosa occur in enriched lakes and are tolerant to low light availability BovoScomparin and Train 2008).…”
Section: Discussionsupporting
confidence: 88%
“…This result was similar to that reported by Fonseca and Bicudo (2008), considering negative correlation with cyanobacteria total density and Willame et al (2008), who considered negative correlation with cyanobacteria efficient in competing for N. This result suggests that these filamentous species preferred the oxidized form of nitrogen (nitrate). However, studies highlighted that C. raciborskii abundance decreases with the decreasing inorganic nitrogen (TONETTA et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Although phosphorus is frequently considered as the most important limiting factor for algal growth (DELAZARI-BARROSO et al, 2007), nitrogen limitation is recognized as the ideal condition for the occurrence of cyanobacterial blooms, reported in several studies in eutrophic ecosystems, highlighting the predominance of heterocystous species (MOURA et al, 2007a, 2007b, DELAZARI-BARROSO et al, 2007BICUDO, 2008, BEZERRA et al, 2014, COSTA et al, 2014, including reservoirs of Northeastern Brazil, probably due the high availability of phosphorous . Nevertheless, studies also demonstrated the predominance of cyanobacteria under phosphorus limiting conditions (CHELLAPPA et al, 2008, FIGUEREDO;GIANI, 2009) or found no relationship between cyanobacterial dominance and TN: TP ratio in eutrophic reservoirs .…”
Section: Discussionmentioning
confidence: 99%
“…Cylindrospermopsis raciborskii is characterized by its association with high TN/TP ratios (Briand et al, 2002b), while P. agardhii appears to be favoured by low TN/TP ratios (Ru¨cker et al, 1997). Moreover, both species are able to develop very abundant populations or even form intense blooms (Berger, 1975(Berger, , 1989De Souza et al, 1998;Fonseca & De M. Bicudo, 2008). Occurrence of C. raciborskii with mass development of P. agardhii is known in Polish lakes (Stefaniak & Kokocin´ski, 2005;Pelechata et al, 2006;Kokocin´ski et al, 2009) but documented examples of abundant coexistence of these species are sparse Crossetti & De M. Bicudo, 2008).…”
Section: Introductionmentioning
confidence: 99%